2022
DOI: 10.1007/s11295-022-01571-w
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTLs for citrus quality traits throughout the fruit maturation process on clementine (Citrus reticulata × C. sinensis) and mandarin (C. reticulata Blanco) genetic maps

Abstract: Citrus fruit quality is defined as the combination of physical and chemical traits; some of which may change during the ripening phase, e.g., acidity and sugar content. A clear understanding of their genetic control would be very helpful for marker-assisted breeding programs especially with regard to the juvenile phase and some reproductive features that hamper the selection of improved hybrids. A genetic study was thus performed on the heredity of quality traits and QTL detection based on segregation in a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In Citrus, four significant QTLs for fruit weight were identified using GWAS analysis, in part confirming previous reports [79]. Major QTLs (R 2 ≥ 30%) were detected for equatorial diameter [108]. A QTL for yield was detected on LG2 in coffee, and it was significant in two different locations.…”
Section: Fruit Size and Weightsupporting
confidence: 84%
“…In Citrus, four significant QTLs for fruit weight were identified using GWAS analysis, in part confirming previous reports [79]. Major QTLs (R 2 ≥ 30%) were detected for equatorial diameter [108]. A QTL for yield was detected on LG2 in coffee, and it was significant in two different locations.…”
Section: Fruit Size and Weightsupporting
confidence: 84%
“…However, the complexity of an aromatic profile based on numerous compounds, some of which are at very low concentrations and sometimes undetectable, cannot be reproduced because most of the QTLs of these compounds are not detectable. Previous studies also revealed the complexity of the inheritance of sugar content and acidity, which are other key components of fruit quality [ 32 , 33 , 34 , 35 ]. QTLs vary among studies, as well as over the fruit-ripening period.…”
Section: Discussionmentioning
confidence: 99%
“…The observed segregation for major compounds suggests that essential oil production could also have polygenic control. In citrus, the genetic architecture of internal and external quality traits of mandarin fruits is being increasingly studied [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of BLUPs improved the QTL detection power by blurring the environmental variance. Indeed, several studies have demonstrated the effectiveness of using BLUPs for QTL localization in different fruit species such as apple (Segura et al, 2009), citrus (Khefifi et al, 2022), and grapevine , where the experimental material had been phenotyped under different environments. The observed instability in common QTL detection might be due to a complex quantitative genetic model and different physiological mechanisms in the determination of different fruit-quality components in response to environmental variations between years (Fanizza et al, 2005).…”
Section: Linkage Mapping and Quantitative Trait Loci Analysismentioning
confidence: 99%